Ethics that matters : African, Caribbean, and African American sources - Riggs, Marcia; Logan, James Samuel (Fortress Press, 2012)
In light of globalization, ongoing issues of race, gender, and class, and the rapidly changing roles of institutions, this volume asserts that Christian social ethics must be reframed completely. Three questions are at the heart of this vital inquiry: How can moral community flourish in a global context? What kinds of leadership do we need to nurture global moral community? How shall we construe social institutions and social movements for change in the twenty-first century?